Membrane adsorbers for low-pressure metal ion capture - McKean, Thomas; Wilmoth, Courtney; Wickramasinghe, S. Ranil; Hestekin, Jamie (Frontiers in Membrane Science and Technology, 2025)
Heavy metal ions are notoriously difficult to remove from water systems without the infrastructure present at a drinking water treatment plant. This work aimed to develop membrane adsorbers capable of capturing heavy metals at low pressure to avoid the need for extensive infrastructure. Removal of copper as a representative heavy metal was investigated. Membrane adsorbers were fabricated by using photo-initiated radical polymerization to graft glycidyl methacrylate (GMA) from the surface of polyethersulfone microfiltration membranes. The GMA modified membrane was sulfonated through an epoxide ring opening reaction to introduce sulfonic acid groups. The effect of grafting time and temperature on the degree of grafting and membrane performance (permeability and adsorption capacity) were determined. The reactions conditions that provided best performance were 4 min UV exposure at 35 °C. Under these conditions, the degree of grafting was 9% while maintaining a low operating pressure of 0.1 bar. Five and 6 min of UV exposure time increased the DOG to 19% and 41%, respectively, but compromised low pressure operation. Membrane surface properties were characterized by Fourier transform infrared spectroscopy and scanning electron microscopy. Membrane performance was investigated by determining membrane permeability and static and dynamic capacity. The dynamic binding capacity was 64.05 ± 0.6 mg Cu/g grafted weight. Using membranes in series demonstrated linear scaleup. Further at a flux of 135 Lm−2h−1 the feed pressure was under 0.15 bar ensuring low pressure operation. These results highlight the potential of membrane adsorbers for low pressure removal of heavy metals.